The use of tranquilizing agents in the treatment of pertussis - Tevetoğlu, Fethi (The Turkish Journal of Pediatrics, 1959)
Sixty pediatric patients with pertussis were divided into three therapeutic groups, the first (Group A) receiving chloromycetin and prochlorperazine; the second (Group B), chloromycetin and chlorpromazine; and the third (Group C), chloromycetin alone. The addition of the tranquilizing drugs in Groups A and B provided rapid control of vomiting, and in these patients most symptoms (vomiting, paroxysmal cough, cyanosis, whoop, convulsive episodes and anorexia) diminished considerably during the first twenty-four hour period. After five to ten days of treatment all patients in Groups A and B were asymptomatic, and there were no sequelae or complications of therapy. Patients in Group C, treated with chloromycetin alone, experienced frequent episodes of vomiting, severe coughing spells and cyanosis during the course of the disease. The antibiotic often could not be retained because of vomiting. Thirty per cent of the patients in Group C developed complications, including pulmonary collapse, inguinal hernia, anorexia, anemia and malnutrition. In combination with chloromycetin, prochlorperazine and chlorpromazine appear to provide a successful method of treating pertussis.